2007
DOI: 10.1364/oe.15.016748
|View full text |Cite
|
Sign up to set email alerts
|

Periodic and quasi-periodic non-diffracting wave fields generated by superposition of multiple Bessel beams

Abstract: We discuss a computer generated hologram whose transmittance is defined in terms of the Jacobi-Anger identity. If the hologram is implemented with a continuous phase spatial light modulator it generates integer-order non-diffracting Bessel beams, with a common asymptotic radial frequency, at separated propagation axes. On the other hand, when the hologram is implemented with a low-resolution pixelated phase modulator, it is possible to generate multiple Bessel beams with a common propagation axis. We employ th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…6, the intensity distributions of a DNB with n = 42 and varying m as well as of a (modulated) Bessel beam of order m are depicted. It was already shown that DNBs can be implemented by interfering nondiffracting Bessel beams [35], which indicates that nondiffracting beam families are transformable among each other. The described behavior of DNBs implies that also Bessel beams can be developed in the frame of DNBs.…”
Section: Quasiperiodic Transverse Intensity Modulationmentioning
confidence: 99%
“…6, the intensity distributions of a DNB with n = 42 and varying m as well as of a (modulated) Bessel beam of order m are depicted. It was already shown that DNBs can be implemented by interfering nondiffracting Bessel beams [35], which indicates that nondiffracting beam families are transformable among each other. The described behavior of DNBs implies that also Bessel beams can be developed in the frame of DNBs.…”
Section: Quasiperiodic Transverse Intensity Modulationmentioning
confidence: 99%
“…The OVs are generated in a variety of methods. Synthetic holograms [23,24], laser mode separation [25,26], computer-generated holograms [27], phase masking [28], hologram superimposing Bessel beams [29], holographic meta surface liquid-crystal spatial light modulator (LC-SLM) [30], phase-only SLM [31,32], multiple plane wave interference [33], and deformable mirrors [9]. LC-SLM methods have shown to generate perfect OV [30,34] and gradient-rotation split-ring antenna metasurfaces have shown to generate high purity OVs [35], while the use of spiral phase plates is one of the most often used passive methods for the generation of OVs [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…The unique optical properties of the optical vortices have been widely used in applications such as optical tweezers [5][6][7][8], image processing [9][10][11], communication systems in free space [12][13][14], and optical fibers [15,16]. Motivated by these applications several methods for generating the optical vortex beam have been proposed [17][18][19][20][21][22][23][24][25][26][27]; however the diameter of these optical vortices is related to their topological charges. This property causes difficulties to achieve a high spatial accuracy and high orbital angular momentum coupling optical vortices into a fiber.…”
Section: Introductionmentioning
confidence: 99%